Assessing Resource Utilization during Vigilance Using Transcranial Doppler: The Effects of Extraversion. (September 2013) - Nguyen, Cynthia; Satterfield, Kelly; Bellows, Brooke; McKnight, Patrick; Shaw, Tyler H.
Although automated systems have decreased the information-processing load on workers and have increased productivity, studies have shown that automation can have serious drawbacks, such as reductions in operator vigilance that can lead to decreased detection of critical events. Transcranial Doppler sonography (TCD) is a tool used to measure cerebral blood flow velocity (CBFV), and previous studies have shown that TCD can be used to examine attentional resource utilization and allocation during vigilance task performance. This study was designed to assess the attentional resource utilization of an individual difference measure that has shown to be associated with vigilance performance efficiency, extraversion. Twelve extraverts and thirteen introverts monitored a 60-min vigilance task for critical signals, which in this case, was the absence of a line on one of the five circles displayed on a computer monitor. CBFV and correct detections over six 10-min periods were used as the units of analysis. While a vigilance decrement was observed, there was no difference in detection efficiency between extraverts and introverts. The results pertaining to the CBFV measure reveal a significant hemisphere x personality interaction, such that the lateralization effect often present in vigilance was restricted to introverts. The results are interpreted in terms of findings suggesting that bilateral activation is a function of task difficulty: extraverts were recruiting mental resources from both the left and right cerebral hemispheres while introverts were using resources from only the right hemisphere. These findings suggest that the TCD measure is diagnostic of resource allocation associated with individual differences in vigilance.